2018
DOI: 10.1002/prep.201800054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Titanium and Zirconium Hydrides on the Parameters of Confined Explosions of RDX‐Based Explosives – A Comparison to Aluminium

Abstract: Overpressure and temperature histories of explosions of RDX‐based non‐ideal explosives containing 15, 30 and 45 % of Al, (Al/ZrH2), TiH2 and ZrH2 were measured in a closed chamber filled with argon and air. The solid post‐explosion products were analysed to determine their elemental and phase composition and characterise their morphology. The experimental explosion parameters were compared with those obtained from thermochemical calculations. The results obtained indicate that all the additives react both with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Our previous paper [23] showed that the calculated equilibrium overpressure after detonation of 50 g RDXph charge in the chamber filled with argon was 0.78 MPa. The mass of RDXph in the charges tested in this work was 35 g (70 % out of 50 g), so that, if the additives are chemically inert, then the overpressure in the chamber should not be higher than 0.55 MPa.…”
Section: Resultsmentioning
confidence: 97%
“…Our previous paper [23] showed that the calculated equilibrium overpressure after detonation of 50 g RDXph charge in the chamber filled with argon was 0.78 MPa. The mass of RDXph in the charges tested in this work was 35 g (70 % out of 50 g), so that, if the additives are chemically inert, then the overpressure in the chamber should not be higher than 0.55 MPa.…”
Section: Resultsmentioning
confidence: 97%
“…However, as a type of watercontaining explosive, the introduction of water would reduce its explosion energy in spite of enhancing the safety, which largely limits the further application of emulsion explosives [3,4]. To improve the explosion energy of emulsion explosives, some high-energy additives such as metal powders and hydrogen storage alloy powders were added to enhance their detonation performance [5][6][7]. As a kind of high energy powders, boron powder is widely used in the field of solid propellants and explosives for its advantages in mass specific heat (58.81 MJ/kg), volume specific heat (137.94 kJ/cm 3 ) and combustion heat (58 MJ/kg), which could further improve the output energy of explosives when compared with aluminum and magnesium powders.…”
Section: Introductionmentioning
confidence: 99%
“…Cudziło et aI. observed that the addition of titanium hydride to sub-oxygenated explosive charges decreased their detonation heats, and even noticed the presence of unreacted hydride in the detonation products [26]. Dietzel and Leslie were the first to patent the use of mixtures of titanium hydride and potassium perchlorate (KP) as energetic compositions, with low sensitivity to static electricity and spark, and high autoignition temperature, in igniters [27].…”
Section: Introductionmentioning
confidence: 99%